The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1ta10442j
|View full text |Cite
|
Sign up to set email alerts
|

Boosting and regulating solar energy conversion performance of delafossite AgFeO2 by spin polarization

Abstract: Spin polarization plays an important role in spintronics, nanoelectronics, new energy, and other emerging high-tech fields. However, due to the lack of suitable research targets and insufficient understanding of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that materials with electron spin structure can produce mixed phases with direct and indirect band gaps due to the influence of electron spin. 27 In the case of the synthesized materials, Tauc plot (Fig. 4b and d) analysis revealed that both direct and indirect bandgap CoSe 2 were smaller than those of FeSe 2 and FeCoSe 2 .…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies have shown that materials with electron spin structure can produce mixed phases with direct and indirect band gaps due to the influence of electron spin. 27 In the case of the synthesized materials, Tauc plot (Fig. 4b and d) analysis revealed that both direct and indirect bandgap CoSe 2 were smaller than those of FeSe 2 and FeCoSe 2 .…”
Section: Resultsmentioning
confidence: 83%
“…The structure of the 3R-polymorph of silver ferrite delafossite, AgFeO 2 , is shown in Figure . This compound has been investigated for a range of potential applications, including as a cathode material in lithium-ion batteries, as nontoxic and biocompatible semiconductor nanoparticles, as components in solar energy conversion, and as a host for multiferroic behavior . Nanoparticles of AgFeO 2 , which have a direct band gap of 2.0 eV, have also been investigated as magnetically guidable photocatalysts for the production of reactive oxygen species within cancer cells …”
Section: Introductionmentioning
confidence: 99%
“…Among various delafossite oxides, copper-based delafossite oxides stand out as promising candidates due to their desirable electrical and optical characteristics. The copper-based delafossite oxide, specifically CuMO 2 (where M represents Al, Ga, Fe, Co, Mg, Fe, Cr…), has attracted considerable attention for diverse applications such as batteries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], luminescent materials [ 16 , 17 , 18 , 19 , 20 , 21 ], thermoelectrics [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ], solar energy conversion and photocatalysis [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], hydrogen production through water splitting using photocathodes [ 36 , 37 , 38 , 39 , 40 , 41 ], and gas sensors [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In this study, we focus on the CuCoO 2 compound, in view of intriguing structural, optical, and electrical properties; it has only been studied in a limited number of publications, and in most of them, the CuCoO 2 compound has shown interesting properties to be treated as a possible material in photovoltaic solar cells [ 50 ,…”
Section: Introductionmentioning
confidence: 99%
“…. ), has attracted considerable attention for diverse applications such as batteries [9][10][11][12][13][14][15], luminescent materials [16][17][18][19][20][21], thermoelectrics [22][23][24][25][26][27][28], solar energy conversion and photocatalysis [29][30][31][32][33][34][35], hydrogen production through water splitting using photocathodes [36][37][38][39][40][41], and gas sensors [42][43][44][45][46][47][48][49]. In this study, we focus on the CuCoO 2 compound, in view of intriguing structural, optical, and electrical properties; it has only been studied in a limited number of publications, and in most of them, the CuCoO 2 compound has shown interesting properties to be treated as a possible material in photovoltaic solar cells [50][51][52][53][54]…”
Section: Introductionmentioning
confidence: 99%